Metal Matrix Composites - Khanna, Virat; Sharma, Prianka; Kumar, Santosh (Bentham Science Publishers, 2024)
This book provides a comprehensive overview of metal matrix composite manufacturing, including fabrication methods, characterization techniques, and manufacturing applications. 10 chapters cover fundamental and applied topics on matrix metal composites. The book is a resource for all readers seeking to gain an in-depth understanding of metal matrix composites with its relevance to the modern industry. Key Features - Includes fully referenced contributions by experts in materials science - Provides an introduction to the subject, and a future prospective for a broad range of readers - Reviews current knowledge on fabrication techniques and structure property relationships of metal matrix composites - Includes dedicated chapters for reinforced composites (carbon fiber, carbon nanotubes, aluminium) - Includes guidance on material wear and tear and - Provides an investigation for process optimization for EDM for newly developed composites It is designed to be an essential resource for students and professionals in the field of materials science and engineering, as well as researchers and engineers working on metal matrix composite in manufacturing industries. Readership Students and professionals in the field of materials science and engineering; researchers and engineers working on metal matrix composite in manufacturing industries.